X-ray Crystal Structure of Bovine 3 Glu-Osteocalcin - Malashkevich, Vladimir N. (Biochemistry, 2013)
The 3 Glu form of osteocalcin (3 Glu-OCN) is increased in serum during low vitamin K intake or oral anticoagulant use (warfarin). Previous reports using circular dichroism show it is less structured than 3 Gla Ca(2+)-osteocalcin and does not bind strongly to bone mineral. Recent studies have suggested a role for 3 Glu-OCN as a potential regulator of glucose metabolism. A G-protein-coupled receptor, GPRC6a, found in the pancreas and testes was identified as the putative osteocalcin receptor. The purpose of this study is to determine the high-resolution structure of bovine 3 Glu-OCN, using X-ray crystallography, to understand molecular interactions with mineral and the GPRC6a receptor. Diffraction quality crystals of thermally decarboxylated bovine osteocalcin were grown, and the crystal structure was determined to 1.88 Å resolution. The final refined structure contained residues 17–47 and, like 3 Gla Ca(2+)-OCN, consisted of three α-helices surrounding a hydrophobic core, a C23–C29 disulfide bond between two of the helices, and no bound Ca(2+). Thus, the helical structure of 3 Glu-OCN is Ca(2+)-independent but similar to that of 3 Gla Ca(2+)-OCN. A reduced level of mineral binding could result from a lower number of Ca(2+) coordinating ligands on 3 Glu-OCN. The structure suggests the GPRC6a receptor may respond to helical osteocalcin and will aid in providing molecular mechanistic insight into the role of 3 Glu-OCN in glucose homeostasis. [Image: see text]